Introducing authoritarian diasporas: causes and consequences of authoritarian elite dispersion. Issue 3 (3rd April 2021) - Loxton, James; Power, Timothy
ABSTRACT: Scholarship on democratization has made significant progress in theorizing the trajectories of former authoritarian elites, with considerable attention given to authoritarian successor parties in particular. However, the literature has largely failed to contend with cases in which the cohort of former authoritarian officials scatters widely across the political system. We identify these patterns of dispersion as authoritarian diasporas and investigate their potential causes and consequences. In launching a new research agenda on this understudied phenomenon, we review not only contending causes for elite defection from authoritarian ruling parties, but also various options for political reincarnation of these officials (e.g. new party creation, colonization of existing parties, and independent candidacies). We hypothesize that the initial decision to defect is contingent upon a number of intervening regime- and individual-level variables. The destinations of former authoritarian incumbents are shaped by regime legacies, personal political resources, and institutional rules. We conclude by reflecting on the ways in which authoritarian diasporas are likely to be more harmful to democracy than the continued presence of an authoritarian successor party.